Nonlinear relationship between financial development and economic growth : evidence from post global financial crisis panel data - Elya Nabila Abdul Bahri; Abu Hassan Shaari Md Nor; Tamat Sarmidi; Nor Hakimah Haji Mohd Nor (Penerbit Universiti Kebangsaan Malaysia, 2018)
Existing studies find that the nonlinear relationship between financial development and economic growth is inverted U-shaped or there exist Kuznets curve, where financial development harm growth after surpassed the threshold point. The objective of this study is to re-estimate the existing relationship between financial development and economic growth for 65 developing countries for the period post 2007-2008 Global Financial Crisis starts from 2009-2015 using Generalized Method-of-Moment (GMM). Three financial development indicators namely, domestic credit to private sector (DCPS), liquid liabilities (LL) and private credit to deposit money (PCDM) are used in this study. However, our findings are contrary to the previous study. Interestingly, our result shows that the nonlinear relationship between financial development and economic growth is U-shaped for all indicators. In other words, financial development accelerated economic growth after reaching the turning point. The results of U-test of Lind and Mehlum (2010) confirms that the U-shaped relationship exist. It shows that the higher financial development enhance the performance of economic growth. Thus, our results challenge the previous findings and recommend for policy review.